Characteristics of subclinical thyroid dysfunction in coastal communities in Malaysia - Shahar, Mohammad Arif; Saud Ghani, Siti Liyana; Omar, Ahmad Marzuki; Abdul Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine & Metabolic Society (MEMS), 2016)
Objectives. To describe the characteristics of subclinical thyroid disorders in the coastal communities of Malaysia. This study is part of a nationwide study looking into the prevalence of thyroid disorders.